2018
DOI: 10.1136/bjophthalmol-2017-311683
|View full text |Cite
|
Sign up to set email alerts
|

Modified everting sutures: an alternative treatment for mild to moderate epiblepharon

Abstract: The modified everting suture procedure is a safe, effective, quick and relatively easy procedure for selected patients with mild to moderate epiblepharon, who are undergoing general anaesthesia for surgical correction of their coexisting ophthalmic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…First of all, when we excluded children with mild epiblephaorn, the prevalence decreased to 11.9% which is similar to 13.8% as reported in the Japanese children. Second, in their study, the cilia-cornea touching was con rmed only when the cornea is positively stained after topical uorescein staining; whereas, later studies by Khwang S. et al and Young S. et al indicate that a considerable number of epiblepharon (usually mild epiblepharon) may not have the ocular manifestation of corneal erosion that could be stained with uorescein 8,13 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…First of all, when we excluded children with mild epiblephaorn, the prevalence decreased to 11.9% which is similar to 13.8% as reported in the Japanese children. Second, in their study, the cilia-cornea touching was con rmed only when the cornea is positively stained after topical uorescein staining; whereas, later studies by Khwang S. et al and Young S. et al indicate that a considerable number of epiblepharon (usually mild epiblepharon) may not have the ocular manifestation of corneal erosion that could be stained with uorescein 8,13 .…”
Section: Discussionmentioning
confidence: 85%
“…According to Khwarg's classi cation, the severity of skinfold was categorized into 4 classes according to its height and the degree to which it concealed the eyelid margin in the primary eye position 8 ; the severity of cilia-cornea touch was classi ed into 3 classes according to the area of inverted cilia touching the ocular surface in the primary position ( Fig. 1) 8 .The children were thereafter considered to have mild epiblepharon if they had any signs of class , moderate epiblepharon if they demonstrated any signs of class , and severe epiblepharon if they presented any signs of class or worse 13 . The diagnosis of lower eyelid epiblepharon was performed independently by two authors (ZD and CS) where disagreement was resolved by discussion with a senior specialist (XL).…”
Section: De Nitions Of Lower Eyelid Epiblepharonmentioning
confidence: 99%
“…The relatively lower prevalence in Noda's study is possibly owing to that they adopt a relatively stricter criteria for disease diagnosis where the widely-accepted Khwarg's classi cation has yet been established. In Noda's study, the cilia-cornea touching was con rmed only when the cornea was positively stained after topical uorescein staining; whereas, later studies by Khwang S. et al and Young S. et al indicated that a considerable number of epiblepharon (usually mild epiblepharon) may not have the ocular manifestation of corneal erosion that could be stained with uorescein 8,13 . In addition, when we excluded children with mild epiblephaorn, the prevalence decreased to 11.9% which was similar to 13.8% as reported in Noda's study.…”
Section: Discussionmentioning
confidence: 97%
“…Lower eyelid epiblepharon is diagnosed as a redundant skinfold in the lower eyelid with inverted eyelashes touching the corneal surface, but no inward rotation of eyelid margin 3 . According to Khwarg's classi cation, the severity of skinfold was categorized into 4 classes according to its height and the degree to which it concealed the eyelid margin in the primary eye position 8 ; the severity of cilia-cornea touch was classi ed into 3 classes according to the area of inverted cilia touching the ocular surface in the primary position (Figure 1) 8 .The children were thereafter considered to have mild epiblepharon if they had any signs of class , moderate epiblepharon if they demonstrated any signs of class , and severe epiblepharon if they presented any signs of class or worse 13 . The diagnosis of lower eyelid epiblepharon was performed independently by two authors (ZD and CS) where disagreement was resolved by discussion with a senior specialist (XL).…”
Section: De Nitions Of Lower Eyelid Epiblepharonmentioning
confidence: 99%
“…Young et al 7 report a modified technique of everting sutures for mild to moderate epiblepharon with a good success rate and low recurrence rate. The authors only included patients with mild epiblepharon (class 1 cilia-corneal touch, class 1 skin fold or class 1 keratopathy) and moderate epiblepharon (class 2 cilia-corneal touch, class 2 skin fold or class 2 keratopathy).…”
mentioning
confidence: 99%